Pengaruh Faktor Sosial Ekonomi Petani Terhadap Produksi Usahatani Jagung Di Desa Rejuno Kecamatan Karangjati Kabupaten Ngawi - Rudy Bintoro Hari Larmintho (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
Abstract— The purpose of this study was to determine the effect of socio-economic factors on corn farming production in Rejuno Village, Karangjati District, Ngawi Regency, East Java. The research was conducted in Rejuno Village, Karangjati District, Ngawi Regency, from October to December 2020. The population in this study were all maize farmers in Rejuno Village. The sampling technique in this study was using simple random sampling technique.The results showed that (1) Corn farming in Rejuno Village, Karangjati District, Ngawi Regency was carried out in 4 (four) stages, namely land preparation and processing, planting was carried out twice per planting season, maintenance was carried out manually and harvesting was carried out manually; (2) Partially the variables of land area, seeds, and experience have a significant effect on maize farming production, while the number of family dependents and age have no significant effect on maize farming production. While simultaneously the variables of land area, seeds, labor force, experience, and age have a significant effect on the production of maize farming in Rejuno village, Karangjati sub-district, Ngawi district. Keywords—: socio-economic factors; corn farming production.